Field efficacy of different insecticides against jassid (Amrasca biguttula biguttula) in brinjal at Gauradaha, Jhapa, Nepal - Tamang, Asmita; Chaudhary, Pratima; Acharya, Manju; Pokharel, Mikun; Soti, Ankit (Journal of Agriculture and Applied Biology, 2025)
Jassid (Amrasca biguttula biguttula) is regarded as the most harmful sap-sucking pest affecting the brinjal crop. This research evaluated the efficacy of insecticides against Jassid in seasonal brinjal in open fields at Gauradaha, Jhapa, Nepal, from January to April 2023. We selected a registered hybrid variety and designed the experiment with seven treatments, each replicated three times. The treatments were: T1: Emamectin benzoate 5% WDG-0.625 g/plot, T2: Spinosad 45% SC-0.5 ml/plot, T3: Neem oil 5000 ppm-8 ml/plot, T4: Fipronil 0.3% GR-40 g/plot, T5: Beauveria bassiana-1.3 g/plot, T6: Imidacloprid 70% WG-0.14 g/plot, and T7: Untreated or Control (water spray)-2 l/plot. Treatments were applied 3 times using a foliar spray method. Data regarding the Jassid population before spraying insecticides and after the 2nd, 4th, and 6th days of spraying were recorded. Data were collected, log10 transformed, and analyzed using ANOVA in GenStat (15th edition), with mean separation by Duncan’s Multiple Range Test (DMRT). The results show that Imidacloprid was the most effective against Jassid, with mean mortality of 82.04%, 40.35%, and 42.13% followed by Fipronil with 33.12%, 12.56%, and 17.86%. The highest yield (14.32 Mt/ha) was recorded from Imidacloprid 70% WG followed by Beauveria bassiana (13.82 Mt/ha). Regarding the B: C ratio, Imidacloprid 70% WG was the superior treatment with the highest value (2.5) followed by Fipronil 0.3% GR (2.1). The highest length (20.48 cm) and diameter (4.5 cm) were observed in Imidacloprid and Fipronil, while the lowest was recorded in Emamectin benzoate (12.14 cm) and Control (3.6 cm), respectively. These findings demonstrate that Imidacloprid significantly reduces Jassid populations and enhances brinjal productivity and economic returns, making it a superior choice for pest management in brinjal cultivation in Jhapa, Nepal.